PEMANFAATAN SUSU FULL CREAM DAN MINYAK SAWIT MERAH DALAM PEMBUATAN ES KRIM UBI JALAR UNGU (Ipomoea batatas L.) - Chandra, Rani; Herawati, Netti; Zalfiatri, Yelmira (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2017)
The purpose of this research was to obtain the formulation of full cream milk and red palm oil in the making of ice cream with the best of value fat content, protein content, overrun, melting point, total solids, and organoleptic test. This research used a Completely Randomized Design (CRD) with four treatments and four replications. The treatments were K1 (Full cream milk : red palm oil = 100% : 0%), K2 (Full cream milk : red palm oil = 97% : 3%), K3 (Full cream milk : red palm oil = 94% : 6%),K4 (Full cream milk : red palm oil = 91% : 9%). The data obtained were analysed statistically by using Analysis of Variance (ANOVA). If the F count was greater than or equal to F table then continued with DNMRT test at 5% levels. The results of this research showed that the formulation of full cream milk and red palm oil in the making of ice cream indicated significant effect (P<0,05) on fat content, protein content, overrun, melting point, total solids, and organoleptic test. The treatment K3 having overrun 19.59%, melting point 12.20 minutes, fat content 17.91%, protein content 2.86%, total solids 28.99%. The ice cream obtained from K3 was also preferred by panelists than other treatments especially for colour and flavour of description test and taste, flavour, and acceptance test of hedonic. Keywords : Full cream milk, red palm oil, and ice cream.